THE CAUSES, PATHOGENESIS, CLINICAL MANIFESTATIONS, AND LABORATORY DIAGNOSIS OF THROMBOCYTOPENIA IN PREGNANT WOMEN - Zaynutdinova Dilafruz Latibovna; Turdibekov Gulomjon Muxiddin ogli (Scholar Express Journals, 2025)
Thrombocytopenia in pregnant women is classified into immune thrombocytopenia developed during pregnancy, pre-existing thrombocytopenia unrelated to pregnancy, and secondary or symptomatic thrombocytopenia. Although numerous studies have been conducted on the causes of thrombocytopenia in pregnant women, and various innovations have been proposed and tested, the results remain quite controversial, debatable, and uncertain. These uncertainties may be resolved in the future through targeted, well-designed, controlled trials, pharmacogenomics, and precision medicine research.
Keywords: hemostasis; pregnancy; thrombocytopenia; bleeding